2018
DOI: 10.1164/rccm.201804-0663oc
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Phenotypes and Mortality in Preserved Ratio Impaired Spirometry in the COPDGene Study

Abstract: PRISm is highly prevalent, is associated with increased mortality, and represents a transitional state for significant subgroups of subjects. Additional studies to characterize longitudinal progression in PRISm are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
177
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 178 publications
(206 citation statements)
references
References 38 publications
22
177
7
Order By: Relevance
“…The results are consistent with the previously reported analysis of the COPDGene study that showed PRISm is an unstable classification which is associated with increased mortality compared to GOLD 1 COPD [12,13]. At 12.4%-12.5%, the prevalence of PRISm was higher in the COPDGene cohort than in the Rotterdam study, which might reflect different sampling schemes (clinical study centres in the former, population-based sampling in the latter) [12,13]. In a recent study in a large Danish cohort, ÇOLAK et al [14] found that even when FEV 1 /FVC >0.8, the presence of chronic respiratory symptoms is associated with respiratory-related hospitalisation and death.…”
supporting
confidence: 93%
“…The results are consistent with the previously reported analysis of the COPDGene study that showed PRISm is an unstable classification which is associated with increased mortality compared to GOLD 1 COPD [12,13]. At 12.4%-12.5%, the prevalence of PRISm was higher in the COPDGene cohort than in the Rotterdam study, which might reflect different sampling schemes (clinical study centres in the former, population-based sampling in the latter) [12,13]. In a recent study in a large Danish cohort, ÇOLAK et al [14] found that even when FEV 1 /FVC >0.8, the presence of chronic respiratory symptoms is associated with respiratory-related hospitalisation and death.…”
supporting
confidence: 93%
“…In our study, subjects with PRISm were similar to typical COPD patients with higher exacerbation frequency, higher comorbidity count, more symptoms, and worse baseline QoL compared to participants that had no airflow obstruction at baseline. Other studies have reported an increase in BMI [27], morbidity [28], increased airway wall thickness [29] and mortality [30] [31] in patients with restrictive spirometry compared to those with no lung disease. Prior data published from COPDGene has also shown that 25% of PRISm individuals developed obstruction between Phase 1 and Phase 2 follow up (31), highlighting the heterogenous nature of this group as well as the potential benefit of routine spirometry in these groups to detect early COPD.…”
Section: Discussionmentioning
confidence: 93%
“…(34,35) Many of these excluded individuals have PRISm, and although they do not meet the diagnostic spirometric criteria for COPD they exhibit similar changes such as small airways disease, emphysema and gas trapping. (4,36,37) Little focus has been given to whether asthma contributes to PRISm, despite high rates of selfreported asthma in other PRISm cohorts (21% in COPDgene (2) ) and in this UKBB cohort reported asthma among PRISm was 18.4%. (4) There are many plausible ways asthma could contribute to both PRISm and airflow obstruction.…”
Section: Discussionmentioning
confidence: 87%